Corporate Social Responsibility and Financial Performance in Nepalese Finance Companies - Pathak, Resham Raj; Panthi, Top Lal (INTELLIGENCE Journal of Multidisciplinary Research, 2026)
This study assesses that the status of amount contributed to the society, Corporate Social Responsibility (CSR) as independent variable and its relationship to the financial performance proxied by net profit, share price, total assets and investment as different forms of dependent variables including employee count as a control variable in selected Nepalese finance companies over the period of 2018 to 2022. Following a deductive research approach with quantitative research design analysis, data from seven finance companies, out of seventeen finance companies were gathered and analyzed using different statistical tools through purposive sampling technique. Results postulate that a significant positive correlation between independent variable named CSR contribution of companies towards their society and dependent variable named financial performance of respective firms, particularly net profit and investment of respective finance companies. Regression results indicate that CSR and employee numbers used as control variable significantly influence on total assets and share prices, explaining up to 86.6% of the variance in the research model. CSR contributions from the selected Nepalese finance companies, increased from Rs. 3.64 million in 2018 to Rs. 5.20 million in 2022 with an annual average growth rate of 10%. Findings of this study indicate that the strengthening in CSR policies and strategic investments in social initiatives campaign can increase financial performance of along with public trust and long-term sustainability for respective firms, providing actionable direction for managers, policymakers and future researchers.